Judges' Philosophical Orientation in Resolving Anti-SLAPP Disputes - Rachmawaty, Rachmawaty; Hartiwiningsih, Hartiwiningsih; Rachmi Handayani, I Gusti Ayu Ketut; Danendra, Ravi (Journal of Human Rights, Culture and Legal System, 2024)
The Anti-SLAPP mechanism in Indonesia still needs to fulfill the four fundamental dimensions of effective Anti-SLAPP. Deciding on Anti-SLAPP in an interim decision is a progressive step because it is a translation of the Anti-SLAPP mechanism in the form of a case dismissal procedure as early as possible. Because no complete rules govern it, this creates confusion for judges. This research aims to analyze the philosophical orientation of judges in resolving disputes for anti-strategic lawsuits against public participation fighters based on Pancasila justice. This research is normative legal research employing two approaches—a philosophical approach and a conceptual approach—and collects and obtains data through direct interviews with judges. This research shows that the Judge's decision in resolving anti-SLAPP disputes based on Pancasila values still needs to be stronger. So, development that damages the environment and benefits the government and corporations will continue. Based on these facts, it is known that the regulation and implementation of anti-SLAPP in Indonesia still do not provide justice for all elements of it because one of the causes is the limitations of the existing anti-SLAPP rules in Indonesia. The factors that caused the Judge's decision not to be based on Pancasila justice can be seen from the lack of legal protection for environmental fighters in Indonesia. Then, the Judge's philosophical orientation in resolving Anti-SLAPP disputes with Pancasila justice refers to the five principles of Pancasila.